2017
DOI: 10.1002/jcla.22366
|View full text |Cite
|
Sign up to set email alerts
|

The correlation between SNPs within the gene of adrenergic receptor and neuropeptide Y and risk of cervical vertigo

Abstract: The SNPs within ADRB2, ADRB1, NPY, and ADRA1A might act as the diagnostic biomarkers and treatment targets for cervical vertigo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…To the best of our knowledge, Runx2 is an important early transcription factor involved in the expression of osteoblast-specific genes, and the differentiation of mesenchymal stem cells into osteoblasts ( 19 ). In addition, Runx2 is hypothesized to serve a primary role in the terminal differentiation of osteoblasts ( 20 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…To the best of our knowledge, Runx2 is an important early transcription factor involved in the expression of osteoblast-specific genes, and the differentiation of mesenchymal stem cells into osteoblasts ( 19 ). In addition, Runx2 is hypothesized to serve a primary role in the terminal differentiation of osteoblasts ( 20 ).…”
Section: Resultsmentioning
confidence: 99%
“…nPY is a neurotransmitter that has dual functions in the regulation of energy consumption and bone mass (11). a previous study determined that SnPs within nPY and neuraminidase (na) were closely associated with the susceptibility and prognosis of patients with cervical vertigo (19). Therefore, nPY and na could be used as diagnostic markers and therapeutic targets for cervical vertigo (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence of etiology collected and 95% CI in pediatric patients were calculated for each study, respectively, with heterogeneity. A total of 37 kinds of etiological diagnoses were categorized as peripheral vertigo disorders, central vertigo disorders, psychogenic vertigo, or other systemic diseases (30,31). In addition, some vertigo symptoms or balance problems that could not be diagnosed accurately were categorized as unclassified vertigo and excluded from data analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Jahn (33) reported that the causes were classified as peripheral vestibular disorders, central vestibular disorders, and non-vestibular dizziness. We separate psychogenic vertigo and other systemic vertigo into two individual groups apart from peripheral vertigo and central vertigo, since more evidence was provided that mental problems and systemic disease interacted closely with vestibular disorders in children (31,34).…”
Section: Discussionmentioning
confidence: 99%